A STUDY OF ASSYRIANS’ LANGUAGE USE IN ISTANBUL - Arikan, Arda; Varli, Ozan; Kürüm, Eyüp Yaşar (Sustainable Multilingualism / Darnioji daugiakalbystė, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*289.15px); top: calc(var(--scale-factor)*75.38px); font-size: calc(var(--scale-factor)*6.96px); font-family: sans-serif; transform: scaleX(1.14338);" role="presentation">http://dx.doi.org/10.1515/sm-2017-0003 Being one of the oldest Christian communities in the Middle East, Assyrians have continued to live in various parts of Turkey for thousands of years. Today, the estimates related to the number of Assyrians living in Turkey vary between 4,000–25,000 while they cannot benefit from the rights put forward by the Lausanne Treaty among which schooling is the most important. Assyrian community can be said to be deteriorating in number. This decline in the number of Assyrians living in Turkey raises the question of whether they could maintain their ethnic identity while maintaining their language (Syriac). No studies so far have been carried out to find out the linguistic practices of Assyrian community living in Turkey, as well as their attitudes toward the languages they use. This study aims at shedding light on the present situation of Syriac used among the Assyrian community living in Turkey. The participants are limited to those living in Istanbul due to practical reasons. In this study, language attitudes and language use practices of Assyrian community living in Istanbul are found out through a language attitudes questionnaire. It is hoped that the results of the study will provide the current situation of the Syriac language in terms of its ethnolinguistic vitality as spoken among the community. It is also hoped that the results of the study will provide useful data for those who would like to help protect the ethnolinguistic identities of Assyrian minority in Turkey, as well as all those dispersed around the world, which seems to have become increasingly important for such a country at the gates of the European Union as Turkey.